Theatre Royal Stratford : 'A better day', a musical play about Keir Hardie, the first ever Labour MP – and for West Ham! (1992)
Red-tinted portrait photo of Keir Hardie alongside line drawing of Big Ben Poster advertising play "A better day", about Labour MP Keir Hardie; shown in the Theatre Royal Stratford East, 5 June-4 July, 1992 PO-1766